Uji Aktivitas Antibakteri Ekstrak Etil Asetat Daun Tigaron (Crataeva nurvala Buch.Ham) Terhadap Bakteri Propionibacterium acnes Dengan Metode Difusi Sumuran - Sari, Putri Kartika; Sari, Novita; Fitriyanti, Fitriyanti (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
Tigaron (C. nurvala buch.Ham.) is a plant can be found in India, Africa, Australia, Japan, Myanmar, Sri Lanka, Malaysia, India and China. Traditionally, the bark, leaves, flowers and root are used in traditional medicine to cure various disease conditions. The leaves of this plant used to treat abscesses, wounds and skin diseases. This study aims to determine of secondary metabolite and antibacterial activity test from ethyl acetate extract of tigaron leaves (C. nurvala buch.Ham.) in inhibiting growth of Propionibacterium acnes with varying concentration which are 0.31 mg/ml, 1.55 mg/ml, 7.75 mg/ml, 38.75 mg/ml, 193.75 mg/ml, negative control Na-CMC 0, 5% and positive control antibiotic clindamycin. Tigaron leaves were extracted using the maceration method using ethyl acetate solvent, secondary metabolite compounds detected using phytochemical screening method and antibacterial activity test using the well diffusion method. The final yield of ethyl acetate extract of tigaron leaves (C. nurvala buch. Ham.) was obtained at 1%. The secondary metabolite contained are alkaloids, flavonoids and steroids. The results showed that concentration of 0.31 mg/mL was included in the weak category inhibition zone (4.97 mm), 1.55 mg/mL (5.97 mm), 7.75 mg/mL (7.08 mm), 38.75 mg/mL (10.02 mm) which was included in the medium category inhibition zone and concentration of 193.75 mg/mL which is included in the strong category inhibition zone, clindamycin antibiotic as a positive control showed a strong zone of inhibition (16.5 mm). Ethyl acetate extract of tigaron leaves (C. nurvala buch.Ham.) can inhibit the growth of Propionibacterium acnes.